Chronic Inflammation in Immune Aging: Role of Pattern Recognition Receptor Crosstalk with the Telomere Complex? - Jose, Shyam Sushama; Bendickova, Kamila; Kepak, Tomas; Krenova, Zdenka; Fric, Jan (Frontiers in Immunology, 2017)
Age-related decline in immunity is characterized by stem cell exhaustion, telomere shortening, and disruption of cell-to-cell communication, leading to increased patient risk of disease. Recent data have demonstrated that chronic inflammation exerts a strong influence on immune aging and is closely correlated with telomere length in a range of major pathologies. The current review discusses the impact of inflammation on immune aging, the likely molecular mediators of this process, and the various disease states that have been linked with immunosenescence. Emerging findings implicate NFkB, the major driver of inflammatory signaling, in several processes that regulate telomere maintenance and/or telomerase activity. While prolonged triggering of pattern recognition receptors is now known to promote immunosenescence, it remains unclear how this process is linked with the telomere complex or telomerase activity. Indeed, enzymatic control of telomere length has been studied for many decades, but alternative roles of telomerase and potential influences on inflammatory responses are only now beginning to emerge. Crosstalk between these pathways may prove to be a key molecular mechanism of immunosenescence. Understanding how components of immune aging interact and modify host protection against pathogens and tumors will be essential for the design of new vaccines and therapies for a wide range of clinical scenarios.